1988
DOI: 10.1111/j.1471-0528.1988.tb12807.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of growth of uterine leiomyomas during pregnancy. A prospective longitudinal study

Abstract: Summary. In a prospective study 32 leiomyomas (fibroids) in 29 pregnant women were examined with ultrasound every 3–8 weeks. Each patient had hetween 3 and 6 scans (mean 4.4) during the course of pregnancy, and 13 patients had a final scan at 6 weeks postpartum. An individual growth curve was established for each tumour and the patterns of growth were analysed. No increase in size during the pregnancy was observed in 25 fibroids (78%). Only 7 (22%) increased in size but by no more than 25% of the initial volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(38 citation statements)
references
References 1 publication
1
35
2
Order By: Relevance
“…Winer‐Muram et al 11 found no change in fibroid size in 92% of patients in a retrospective analysis in which the first ultrasonographic examination was performed between 10 and 20 weeks of gestation, and they did not report a mean gestational age for this study period. Aharoni et al 12, in their prospective study, pointed out that only 22% of uterine myomas showed growth of more than 10% of the initial volume, 59% changed by less than 10% of the initial volume, and 19% decreased in size by more than 10% of the initial volume, but they reported a mean gestational age at enrolment of 14.9 weeks of gestation, which is slightly higher than that reported in our study. Analyzing more recent reports, Neiger et al 5 stated that fibroids do not grow during pregnancy, but they enrolled patients at a later gestational age (14.4 ± 5.4 weeks) than we did, analyzed a mixed population composed of Caucasian and African–American women, and reported only the percentage change in myoma volume.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Winer‐Muram et al 11 found no change in fibroid size in 92% of patients in a retrospective analysis in which the first ultrasonographic examination was performed between 10 and 20 weeks of gestation, and they did not report a mean gestational age for this study period. Aharoni et al 12, in their prospective study, pointed out that only 22% of uterine myomas showed growth of more than 10% of the initial volume, 59% changed by less than 10% of the initial volume, and 19% decreased in size by more than 10% of the initial volume, but they reported a mean gestational age at enrolment of 14.9 weeks of gestation, which is slightly higher than that reported in our study. Analyzing more recent reports, Neiger et al 5 stated that fibroids do not grow during pregnancy, but they enrolled patients at a later gestational age (14.4 ± 5.4 weeks) than we did, analyzed a mixed population composed of Caucasian and African–American women, and reported only the percentage change in myoma volume.…”
Section: Discussioncontrasting
confidence: 84%
“…In contrast, some studies have reported no change or a decrease in volume of uterine myomas during pregnancy5, 6, 11, 12. In our opinion it is very difficult, however, to compare fully our findings with those previously reported, since the majority of previous studies were retrospective and methodologies differed considerably (e.g.…”
Section: Discussioncontrasting
confidence: 80%
“…A longitudinal study of myoma diameter their volume. In a prospective study, Aharoni and coworkers 12 analyzed the increase in volume of my· omas and reported that 78% of the myomas they studied did not change in volume during pregnancy. In our study comparing the total volume of the myomas calculated when the first ultrasonographic scan was obtained with the total volume calculated at the last scan, we noted an increase in volume of 31.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the reported complications relate to submucosal fibroids as demonstrated by this case. Sonographic monitoring of fibroid size in pregnancy has shown that 49–60% of uterine fibroids have a < 10% change in volume, 22–32% increase in size, and 8–27 % decrease in size 2 , 3 , 4 , 5 . The most rapid growth occurs during the first trimester, particularly up until 10 weeks gestation 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Presentations in pregnancy include acute symptoms of degeneration, and urinary retention 6 . Complications are more likely if the fibroid is greater than 200 cm 3 in volume, and less likely when less than 100 cm 3 in volume 2 …”
Section: Discussionmentioning
confidence: 99%